Small-bubble gas injection to mitigate cavitation-induced erosion damage and reduce strain in target vessels at the Spallation Neutron Source. (September 2022) - McClintock, David A.; Liu, Yun; Bruce, Douglas R.; Winder, Drew E.; Schwartz, Richard G.; Kyte, Matt; Blokland, Willem; Sangrey, Robert L.; Carroll, Timothy M.; Long, Cary D.; Jiang, Hao; Riemer, Bernard W.
Graphical abstract: Highlights: The Spallation Neutron Source (SNS) target module design was modified to injected small diameter (<300 µm) helium bubbles into the flowing mercury target material. Photographs of target vessel samples showed significant erosion damage occurred to the inner surfaces of targets operated without gas injection, whereas targets operated with gas injection had greatly reduced or no erosion damage. Quantitative analysis from laser-line scanning showed that targets operated without gas injection had appreciable erosion damage. Similar samples from targets operated with high gas-injection rates had no measurable erosion damage. Strain values in SNS mercury target vessels were measured at several locations during in-situ measurements performed with typical beam pulses. Strain reductions ranging from 40% to 75 % were observed for targets operating with gas-injection rates between 2 and 3 SLPM. Abstract: The effectiveness of small-bubble gas injection to mitigate cavitation-induced erosion damage and decrease strain in Spallation Neutron Source (SNS) target vessels was characterized using photography, laser-line scanning, and in-situ vessel strain measurements. Observations from early targets showed that erosion damage caused appreciable mass loss along the target vessel inner wall. Later target designs incorporated a cavitation mitigation technique called small-bubble gas injection, in which small helium gas bubbles were introduced into the flowing mercury during operation. Samples removed from target vessels after operation revealed that gas injection greatly reduced or eliminated erosion damage. Photographs of the target interiors showed areas where significant erosion damage occurred in targets that were operated without gas injection. The same areas had no observable erosion damage in targets that were operated with gas injection. Laser-line scan measurements were performed on samples from several target vessels operated with and without gas injection to measure the extent of erosion damage and quantify the effect of gas injection on erosion. In-situ strain measurements during operation showed that gas injection reduced the target vessel strain by 25%–75%. These results provide conclusive confirmation that gas injection effectively mitigated erosion damage and reduced strain in SNS target vessels during operation.